(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article defines the types of handicrafts available in the Khorezm khanate and the involvement of women in it. It is highlighted that the main trends of craftsmanship and the new types of professions, which were influenced by the political and socio-political processes at the beginning of the 19th - early 20th centuries in Khorezm oasis.